A new F‐box protein 7 gene mutation causing typical Parkinson's disease. Issue 8 (23rd May 2015) - Lohmann, Ebba; Coquel, Anne‐Sophie; Honoré, Aurélie; Gurvit, Hakan; Hanagasi, Hasmet; Emre, Murat; Leutenegger, Anne L.; Drouet, Valérie; Sahbatou, Mourad; Guven, Gamze; Erginel‐Unaltuna, Nihan; Deleuze, Jean‐Francois; et al.
Abstract Background Recessive mutations in the F‐box protein 7 gene (FBXO7; PARK15) have been identified as a cause of the parkinsonian‐pyramidal syndrome. Here, we report clinical and genetic findings in a Turkish family with novel FBXO7 mutations. Methods Whole exome and targeted Sanger sequencing were performed for genetic analysis in a family with two members affected by Parkinson's disease (PD). All family members underwent detailed clinical, mental, and neurological examination. Results The new p.L34R (c.101 T>G) FBXO7 mutation was detected in a homozygous state in two Turkish sibs with typical levodopa‐responsive PD. Conclusion This is the first time a FBXO7 mutation has been identified that causes a phenotype compatible with typical idiopathic PD and presents with some of its common nonmotor features, such as rapid eye movement sleep behavior disorder, depression, and anxiety. © 2015 International Parkinson and Movement Disorder Society